2008
DOI: 10.1016/j.crme.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of invariant integrals to elastostatic inverse problems

Abstract: A problem of parameters identification for embedded defects in a linear elastic body using results of static tests is considered. A method, based on the use of invariant integrals is developed for solving this problem. A problem for the spherical inclusion parameters identification is considered as an example of the proposed approach application. It is shown that a radius, elastic moduli and coordinates of a spherical inclusion center are determined from one uniaxial tension (compression) test. The explicit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…This property of the RGF was used by Andrieux et al (1999), Goldstein et al (2007Goldstein et al ( , 2008, Kaptsov and Shifrin (2008) for solving some elastostatic inverse problems.…”
Section: Definitions and Equationsmentioning
confidence: 98%
See 2 more Smart Citations
“…This property of the RGF was used by Andrieux et al (1999), Goldstein et al (2007Goldstein et al ( , 2008, Kaptsov and Shifrin (2008) for solving some elastostatic inverse problems.…”
Section: Definitions and Equationsmentioning
confidence: 98%
“…In this case the values S kl are close to the values R 33kl corresponding to an infinite solid containing the crack G and subjected to the uniaxial tension in the direction of the axis x 3 . Calculations fulfilled by Goldstein et al (2007Goldstein et al ( , 2008 for spherical cavities and inclusions showed that a bounded body can be substituted by an infinite solid even if the spherical defect is located not so far from the surface of the body. Taking into account the suppositions, Eqs.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Note that, when the field u r is regular, all the integrals J r i , L r i and M r are zero; otherwise, they are generally non-zero. We will consider the invariant integrals for the sum of fields with superscripts f and r, which will be denoted by a superscript f + r. For the overall field we have (1.4) Integrals corresponding to the interaction between fields with superscripts f and r have the form (1.5) Integrals (1.5) are also invariant; they were introduced earlier 3 and used 12,13 to solve the problem of identifying a spherical cavity and an elastic spherical inclusion.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Для идентификации местоположения одиночных дефектов развит подход, основанный на применении функционала взаимности и инвариантных интегралов, так в работах [1,2] параметры дефекта (координаты центра, линейный размер дефекта) выражаются через отличные от нуля значения функционала взаимности в виде явных аналитических выражений. В работах [3,4] рассматривается задача идентификации конечного числа мелких эллипсоидальных дефектов в анизотропном линейно упругом теле.…”
Section: анализ литературных данных и постановка проблемыunclassified